Isolation of Cowanol from the Garcinia oblongifolia Plant and Evaluation of its in vivo Toxicity and Bone-protective Activity in Medaka Fish (Oryzias latipes) - Nhung, Duong Thi; Manh, Nguyen Huy; Binh, Trinh Thi Dieu; Hiep, Nguyen Dinh; Dien, Pham Phuoc; Bich, Pham Thi; Bich, Pham Thi; Long, Tran Duc; Dong, Thach Ut; Thuy, To Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 4DO - 10.25073/2588-1140/vnunst.5802, 2025)
Garcinia oblongifolia Champ. ex Benth is a plant species widely distributed in Vietnam. It contains xanthones - bioactive compounds known for their potent antioxidant, anti-inflammatory, and anticancer properties. Xanthones have also emerged as potential bone-protective agents. Here, cowanol, a common xanthone, was isolated from the branches of  G. oblongifolia in Binh Dinh Province, with 98.4% purity. The in vivo toxicity and bone-protective activity of cowanol were assessed using medaka ( Oryzias latipes ), a standardized fish model in toxicity and disease research. Acute toxicity was evaluated over a 96-hour exposure period, assessing wild-type embryos (24-120 hours post-fertilization) to concentrations ranging from 2 to 50 µM and larvae (7-11 days post-fertilization) to the doses of  2 to 30 µM. Results showed that cowanol was non-toxic to embryos but exhibited dose- and time-dependent toxicity to larvae, with the lethal concentration 50 (LC 50 ) of 11.4 µM. At the doses of 2 µM or lower, cowanol was safe for medaka larvae. The bone-protective effect of cowanol was investigated using rankl :HSE:CFP transgenic larvae model for osteoporosis. Our findings revealed that cowanol significantly reduced bone damage in the Rankl-induced osteoporosis fish at three tested doses of 0.5, 1.5, or 2 µM with bone protection indexes reaching up to 29.38%. This study highlights the potential exploration of xanthones from Vietnamese plants for therapeutic applications.